Solution Structure of the Cutibacterium acnes-Specific Protein RoxP and Insights Into Its Antioxidant Activity - Stødkilde, Kristian; Nielsen, Jakob Toudahl; Petersen, Steen Vang; Paetzold, Bernhard; Brüggemann, Holger; Mulder, Frans A. A.; Andersen, Christian Brix Folsted (Frontiers in Cellular and Infection Microbiology, 2022)
Cutibacterium acnes is a predominant bacterium on human skin and is generally regarded as commensal. Recently, the abundantly secreted protein produced by C. acnes, RoxP, was shown to alleviate radical-induced cell damage, presumably via antioxidant activity, which could potentially be harnessed to fortify skin barrier function. The aim of this study was to determine the structure of RoxP and elucidate the mechanisms behind its antioxidative effect. Here, we present the solution structure of RoxP revealing a compact immunoglobulin-like domain containing a long flexible loop which, in concert with the core domain, forms a positively charged groove that could function as a binding site for cofactors or substrates. Although RoxP shares structural features with cell-adhesion proteins, we show that it does not appear to be responsible for adhesion of C. acnes bacteria to human keratinocytes. We identify two tyrosine-containing stretches located in the flexible loop of RoxP, which appear to be responsible for the antioxidant activity of RoxP.